Pengaruh Biaya Operasional dan Pendapatan Terhadap Laba Bersih Usaha Wisata Hiu Paus Botubarani - Yusri Harun; Frahmawati Bumulo; Agil Bahsoan; Melizubaida Mahmud; Maya Novrita Dama (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to determine the effect of operational costs and revenue on net profit in the Whale Shark Tourism Business in Botubarani Village, Kabila Bone District, Bone Bolango Regency, Gorontalo Province. The research uses a quantitative approach with a survey method. Primary data were collected through questionnaires distributed to community members involved in the tourism activities, such as boat jockeys and local MSMEs operating around the tourist site. The sample consisted of 40 respondents. The data analysis technique employed in this study is multiple linear regression using the SPSS software. The results indicate that operational costs and revenue simultaneously have a significant effect on net profit. The influence of these two variables on net profit is 38.4%, while the remaining 61.6% is influenced by other factors not examined in this model. These findings suggest that although operational costs and revenue contribute to determining net profit, other external factors play a more dominant role. Therefore, further research is needed to identify and analyze these factors to optimize the management of whale shark tourism businesses and support the sustainability and growth of the local economy.